The Development Of Mobile Learning Media In Physical Education, Sports, And Health (PJOK) Learning For The Second Semester Of Seventh Grade In Junior High School - Shinta, Tasya Dwi; Kurniawan, Candra; Wicaksono, Lungit; Siswoyo, Joan (Jurnal Pendidikan Jasmani (JPJ), 2025)
This study aims to develop mobile learning media for the Physical Education, Sports, and Health (PJOK) subject in the second semester, consisting of five learning topics for seventh-grade junior high school students.The method used is the ADDIE development research method, which consists of five steps: Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques used are interviews and questionnaires. Interviews were used to identify existing problems, while questionnaires were used to validate the feasibility of the developed mobile learning media. The result of this study is a mobile learning media product that can be downloaded from the Google Play Store and installed on Android devices. The developed mobile learning media was considered feasible based on validation and revisions by subject matter experts (91.42%), instructional media experts (97.14%), language experts (97.14%), and PJOK educators (94.28%). In addition, a small-scale trial conducted with students resulted in a score of 92.28%, while in the large-scale trial, teachers gave a score of 96.19% and students 96.08%. Therefore, it can be concluded that the developed mobile learning media is feasible for use as a PJOK learning tool at SMP Negeri 5 Bandarlampung.